VIOLENCE IN ADOLESCENT AFFECTIVE RELATIONSHIPS: A SYSTEMATIC REVIEW - Carvalho, Joice Laine (2018)
The presente study deals with a systematic review aiming to identify the causes, the forms and the agressor of the violence on the teenagers’s datings. The analysis of the fundamental characteristics of violence and adolescence aim at a better understanding of the theme. The data collection was carried out at the SciELO base (publications between 2013 and september 2017). Instituted the inclusion criteria: (a) empirical article; (b) using instruments for data collection; (c) that indicate the causes, the forms and the agressor, eight studies have been analyzed in the whole. These publications used as instruments: Self-filling closed sociodemographic quetionnaires, CADRI (Conflict in Adolescent Dating Relationships Inventory, Conflict Tactics Scale subscale, individual interview and Focus group. The results indicate that violence on the teenagers’s datings suffers the undeniable influence of previous aggressive experiences usually linked to parents, siblings, friends and previous relationships. In the analyzed articles, there is no absolute agreement about the gender prevalence of the aggressor, however the authors understand that violence reflects a pattern of continuity of aggressive behavior. Although there are several forms of violence (sexual, physical, verbal, psychological), it has been concluded that, on several occasions, all are intrinsically linked to psychological violence. Therefore, to eliminate the practice of violence and its reproduction, certain patterns of behavior instituted in our society should be objects of questioning and constant reflection.